The efficiency of the working capital management in the energy sectors in Bangladesh: an empirical study on selected gas distribution companies / Md. Nazmul Huda … [et al.] - Huda, Md. Nazmul; Uddin, Md. Kamal; Ali, Md. Jafor; Alam, Md. Shahbub; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Management of Current assets and Current liabilities are involved in the Working capital management of any business organization. The financial decision regarding the current assets and their utilization plays a crucial role in the solvency, liquidity as well as profitability of the company. The study has been conducted to insight into the management of working capital of the particular gas distribution companies in Bangladesh which are selected on purposive sampling and analysis are conducted especially based on the secondary data collected from annual reports and statements covered a period of 05 years from the financial year 2015-2016 to 2019-2020. The analysis techniques of mean, Average growth rate, standard deviation, coefficient of variation, financial ratio analysis, Motaal’s Comprehensive Test of Liquidity model are used. It is founded that the working capital management of the gas distribution companies is not at a satisfying level especially for state-owned companies, although a new born company (KGDCL) is in a better position comparing with the older one. This study focuses on some techniques which may be followed for management and utilization of current assets and liabilities for enhancing the profitability of the companies to maintain optimum liquidity and solvency.